Analysis of research hotspots in COVID-19 genomics based on citespace software: Bibliometric analysis - Pang, Xue meng; Peng, Zhao yun; Zheng, Xin; Shi, Jing jing; Zhou, Bao chen (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction To analyze the current state, hotspots, and cutting-edge trends of genomics research on the outbreak of Corona Virus Disease 2019 (COVID-19) from 2019 to the present (March 2022). Methods Statistical and visual analysis of COVID-19 genomics results published in the 2019-2022 Web of Science Core Collection Database (WOSCC) was performed using CiteSpace software, including data on countries, institutions, authors, journals, co-citations, keywords, etc. Results A total of 9133 English literature were included. The number of publications has significantly increased in 2021, and it is expected that this upward trend will last into the future. The research hotspots of COVID-19 revolve around quarantine, biological management, angiotensin-converting enzyme-2, RNA-dependent RNA polymerase, etc. Research frontiers and trends focus on molecular docking, messenger RNA, functional receptor, etc. Conclusion The last two years have seen a significant increase in research interest in the field of novel coronavirus pneumonia genomics.